PERAN GURU PAI DALAM MENYIKAPI DAMPAK PERKEMBANGAN TEKNOLOGI KOMUNIKASI PADA SISWA KELAS V SDN TELUKJAMBE I KARAWANG - Nurjaman Nurjaman; Slamet Sholeh; Iqbal Amar Muzaki (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
The problem of this study aims to determine how the role of PAI teachers in addressing the impact of the development of communication technology in fifth grade students at SDN Telukjambe I in the 2019/2020 school year. This study aims: (a) To find out the positive and negative impacts of communication technology development for fifth grade students at SDN Telukjambe I, (b) To find out the objective conditions of PAI teachers at SDN Telukjambe I, and (c) To find out the role of PAI teachers in addressing the impact of the development of communication technology on fifth grade students at SDN Telukjambe I. This type of research is qualitative research. The sources and in this study were divided into two, namely primary data sources namely principals, PAI teacher class V, and homeroom teachers (class Va and Vb) at SDN Telukjambe I, and secondary data sources, namely data in the form of documents there are such as books, theses, archives and school documents that are related to the subject matter being investigated. Data collection techniques used were interviews, observations, and documentation. The results of this study indicate that the role of PAI teachers in responding to the impact of the development of communication technology in fifth grade students at SDN Telukjambe I has succeeded in carrying out several responsibilities and their role towards students in terms of protecting students from the negative effects of communication technology. Before these effects affect students, the role of PAI teachers in providing precautions through several beneficial activities provided to students is urgently needed